The Role of Knowledge Management Operations in Developing Human Resources Capabilities: A Pilot Study Of The Opinions Of A sample Of Managers In Some Industrial Organizations In Dohuk Province Iraqi Kurdistan Region - Mohammed, Ahmed Sulaiman; Al-Azawy, Muhamad Abdul Wahab (Journal of University of Human Development, 2016)
Knowledge Management and its processes represent one of the recent conceptual development in the recent management philosophy , an one of its active practices , and the most consist with the speeding changes in the business world , and its reflects on different tasks and activities of organization which performed by human recourses in according to the abilities and capabilities which they acquired , this lead organizational management to have interest on Knowledge Management and its processes , there is an expect that these process will contribute in developing human recourse capabilities , so this study came to determine the role of the Knowledge Management processes in developing human recourse capabilities in a scientific methodology and field analysis in some industrial organizations in Dohuk Province Iraqi Kurdistan Region , by testing some hypotheses which reflect correlation and effect relationships between the Knowledge Management processes represents ( knowledge acquiring , participating , storing , and applying ) in developing human recourse capabilities in the researched organizations reaching to point down some relevant conclusions , as well as providing some necessary recommendations for the organizations in general and the researched especially.